A prospective study on disorders of sex development in Duhok city, Kurdistan region, Iraq: Genetic, etiology and clinical presentation: Disorders of sex development in Duhok City - M. Hassan, Mohammed; M. Atrushi, Akrem (Cellular and Molecular Biology, 2023)
Disorders of Sexual Development (DSD) encompass all types of intersex cases and have been reported globally. However, in Iraq, studies related to DSD are scanty. The current single-center prospective study was carried out to find out the frequency, genetic and clinical presentation of different types of DSDs in the sample population of Duhok, Iraq. The sample comprises 40 DSD patients who have been referred to Hivi Pediatric Teaching Hospital in Duhok, Kurdistan region, Iraq, from June 2017 to June 2022. We conducted karyotype-based classification, laparoscopic-based internal organ diagnosis and abdominal ultrasound to diagnose DSDs in the target population. Of the total 40 cases, 19 (47.5%) were males, and 21 (52.5%) were females. Among them, 85 % were diagnosed as peno- scrotal hypospadias, 10% had clitoromegaly and the remaining were diagnosed as under-developed female-like genitalia. The majority of the patients were diagnosed with congenital adrenal hyperplasia (CAH) (55%), 37.5% were Testicular Feminization Syndrome (TFS) and the remaining were rare categories that we did not reach final diagnosis. Laparoscopy was done for 77.5 % of the participants of whom 30% had small uterus and ovaries, 25% had Intra-abdominal testes and the remaining had testes &ovaries, Mullerian Inhibitory Factor (MIF) deficiency and TFS. The study found different types of DSDs in the target population that requires both physical and psychological intervention. Future studies should focus on evaluating DSDs in larger populations and at multi-centers to understand the condition’s trajectory in the Iraqi population.